Legal Protection For Syrian Refugees In Jordan - Mefleh O, Hamdon, Hani; Abdo, Alkhaza'leh, Yousef Ahmad; Hassan, Al Smadi, Essa Lafi; Hassan, Al-Jabali, Khaled (Journal of Ecohumanism, 2024)
This Study Aims To Clarify The Nature Of The Rights And Guarantees Provided By International Humanitarian Law To Syrian Refugees In Jordan. Study Employed Both The Legal Method And The Case Study Method. The Findings Indicate That Jordan Is Deeply Committed To Covenants Related To Refugee Rights, Particularly The International Covenant On Civil And Political Rights And The International Covenant On Economic, Social, And Cultural Rights. Jordan Has Ratified Most Of The Relevant Covenants And Agreements. Despite Not Being A Signatory To The 1951 Refugee Convention, Jordan Has Approached The Issue Of Syrian Refugees With A High Level Of Humanitarianism. The Jordanian Government Refers To Syrian Refugees As "Guests" Rather Than Refugees. The Study Recommends The Development Of A Clear And Specific National Strategy For Dealing With Refugees, Particularly If The Crisis Persists For Many Years. Additionally, It Emphasizes The Importance Of Considering The Unique Circumstances Of Asylum Seekers, Such As The Burden Of Proof And Their Psychological Condition.